Comparative Evaluation of the Adsorption Performance of Citric Acid-Treated Peels of Trapa natans and Citrullus lanatus for Cationic Dyes Degradation from Water - Muhammad Sadiq Hussain; Rabia Rehman; Muhammad Imran (Journal of Chemistry)
Various chemicals were explored in chemical combinations with two selected agrowastes in order to optimize, enhance, and improve their biosorption potential for the optimal and effective eradication of noxious, carcinogenic, and malignant cationic and basic dyes from wastewater. In this project, environmentally safe, economic, inexpensive, and widely available peels of Trapa natans (TP) and Citrullus lanatus (CP) were collected, dried, and pretreated with citric acid, revealing promising results. FT-IR and SEM characterizations of chemically changed biosorbents (C-TP and C-CP) have evidenced the presence of more secondary adsorption sites on their surfaces. These acid-modified biosorbents were employed to eliminate the hazardous and toxic basic dyes such as Rhodamine B (RAD) and Brilliant Green Dye (BLG) in batch mode processing. The Langmuir model was best fitted to equilibrium experimental data as compared to Freundlich and Temkin isothermal mathematical models with Qmax of 15.63 and 27.55 mg/g for RAD using C-TP and C-CP, respectively, whereas, for BLG on C-TP and C-CP, it was 128 and 189 mg/g, respectively. Therefore, the mechanism is related to chelation and ion exchange modes between adsorbate molecules and adsorbent surfaces, leading to homogeneous and monolayer adsorption and following pseudo-2nd-order kinetics in the best way. Thermodynamic parameters such as ΔG0, ΔS0, ΔH0, and ΔE0 are determined statistically for the adsorption performance of both novel chemically mutant biosorbents, which reflect that biosorption mechanisms are exothermic as well as spontaneous.